Plus Disease in Retinopathy of Prematurity: More Than Meets the ICROP?. Issue 3 (May 2018) - Ghergherehchi, Layla; Kim, Sang Jin; Campbell, Peter J.; Ostmo, Susan; Chan, Paul R.V.; Chiang, Michael F.
Abstract : Abstract: : Retinopathy of prematurity (ROP), a vasoproliferative retinal disease affecting premature infants, is a leading cause of childhood blindness throughout the world. Plus disease, defined as venous dilatation and arteriolar tortuosity within the posterior retinal vessels greater than or equal to that of a standard published photograph, is the most critical finding in identifying treatment‐requiring ROP. Despite an internationally accepted definition of plus disease, there is significant variability in diagnostic process and outcome, producing variable levels of reported intra‐ and interexpert agreement. Several potential explanations for poor agreement have been proposed, including attention to undefined vascular features such as venous tortuosity, focus on narrower or wider field of view, unfamiliarity with digital images, the magnification and apparent severity of the standard photograph, and cut‐off point differences among experts as to the level of tortuosity and dilation sufficient for "plus disease" along a continuum. Moreover, differences in diagnostic consistency among groups of experts separated both geographically and chronologically have been reported. These findings have implications for clinical care, research, and education, and highlight the need for a more precise definition of plus disease and objective diagnostic methods for ROP.